2017
DOI: 10.1111/1365-2745.12780
|View full text |Cite
|
Sign up to set email alerts
|

The fate of nitrogen inputs in a warmer alpine treeline ecosystem: a 15N labelling study

Abstract: Summary Global warming may accelerate nitrogen (N) transformations in the soil, with potentially large effects in N‐poor high‐elevation ecosystems. To gain insight into the partitioning of inorganic and organic N inputs within the plant–soil system and how warming influences these patterns, we applied a 15N label (15NH4Cl or 15N‐glycine) shortly after snowmelt during the sixth year of experimental soil warming (+4 °C) at treeline in the Swiss Alps. Seven weeks after labelling, approximately 60% of the applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 65 publications
(172 reference statements)
0
5
0
Order By: Relevance
“…In cold regions, N availability is often low in absolute terms, but related to productivity (and the short growing season) the trends are not so obvious (Körner, ; Tranquillini, ) because the nutrient cycle is tuned with the carbon cycle. A recent 15 N tracer study at this site showed that about 60% of N added as NH 4 + or glycine is rapidly immobilized in the soil (Dawes, Schleppi, & Hagedorn, ), as is typical for high elevation ecosystems on acidic soils (Gerzabek, Haberhauer, Stemmer, Klepsch, & Haunold, ). Nevertheless, higher concentrations of N, P and K in leaves, increased soil extractable N and higher δ 15 N values in foliage indicate that the mineral fertilizer indeed increased nutrient availability for plants in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…In cold regions, N availability is often low in absolute terms, but related to productivity (and the short growing season) the trends are not so obvious (Körner, ; Tranquillini, ) because the nutrient cycle is tuned with the carbon cycle. A recent 15 N tracer study at this site showed that about 60% of N added as NH 4 + or glycine is rapidly immobilized in the soil (Dawes, Schleppi, & Hagedorn, ), as is typical for high elevation ecosystems on acidic soils (Gerzabek, Haberhauer, Stemmer, Klepsch, & Haunold, ). Nevertheless, higher concentrations of N, P and K in leaves, increased soil extractable N and higher δ 15 N values in foliage indicate that the mineral fertilizer indeed increased nutrient availability for plants in the present study.…”
Section: Discussionmentioning
confidence: 92%
“…In addition to the positive litter feedback, the more favorable soil climate in the “sheltered” forest than in the “exposed” tundra might have promoted nutrient release and thus, contributed to the increased nutrient availability in the forest (Kammer et al., 2009). In support, a 4°C experimental soil warming at an Alpine treeline induced a 60% increase in KCl‐extractable mineral N contents (Dawes, Schleppi, & Hagedorn, 2017). In comparison, measured increases in temperature between tundra and closed forest of the studied treeline were only 1.3°C during the vegetation period and 0.3°C during winter.…”
Section: Discussionmentioning
confidence: 99%
“…The preference of plants for these ions appears to be related to their mycorrhizal association (Goodale, 2017). Organic forms of N like glycine have mainly been tested in cold ecosystems where they may play a greater role in plant uptake (Sorensen et al, 2008;Dawes et al, 2017).…”
Section: Tracer Applicationmentioning
confidence: 99%